2012
DOI: 10.1111/j.1364-3703.2012.00795.x
|View full text |Cite
|
Sign up to set email alerts
|

OsWRKY22, a monocot WRKY gene, plays a role in the resistance response to blast

Abstract: With the aim of identifying novel regulators of host and nonhost resistance to fungi in rice, we carried out a systematic mutant screen of mutagenized lines. Two mutant wrky22 knockout lines revealed clear-cut enhanced susceptibility to both virulent and avirulent Magnaporthe oryzae strains and altered cellular responses to nonhost Magnaporthe grisea and Blumeria graminis fungi. In addition, the analysis of the pathogen responses of 24 overexpressor OsWRKY22 lines revealed enhanced resistance phenotypes on inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 66 publications
1
40
0
Order By: Relevance
“…Previous data imply that WRKY46 and WRKY72 function in disease resistance signaling. WRKY46 transcript levels were significantly repressed following plant inoculation with avirulent M. oryzae strain CL3.6.7 (Abbruscato et al, 2012), while WRKY72 transcript levels were highly upregulated in 9804 (a japonica rice variety, which was used as the recipient of the maize Rxo1 gene) after inoculation with the bacterial The BPH14 monomers are assembled into a homodimer, which is capable of interacting with WRKY46 and WRKY72. Coexpression of BPH14 is considered to protect WRKY46 and WRKY72 from degradation by the ubiquitin proteasome system.…”
Section: Downstream Signal Transduction and Defense Mechanism Activatmentioning
confidence: 99%
“…Previous data imply that WRKY46 and WRKY72 function in disease resistance signaling. WRKY46 transcript levels were significantly repressed following plant inoculation with avirulent M. oryzae strain CL3.6.7 (Abbruscato et al, 2012), while WRKY72 transcript levels were highly upregulated in 9804 (a japonica rice variety, which was used as the recipient of the maize Rxo1 gene) after inoculation with the bacterial The BPH14 monomers are assembled into a homodimer, which is capable of interacting with WRKY46 and WRKY72. Coexpression of BPH14 is considered to protect WRKY46 and WRKY72 from degradation by the ubiquitin proteasome system.…”
Section: Downstream Signal Transduction and Defense Mechanism Activatmentioning
confidence: 99%
“…Similarly, at least 10 rice WRKYs, i.e. OsWRKY03 [30], OsWRKY71 [31], OsWRKY13 [32], OsWRKY45 [33,34], OsWRK89 [35], OsWRKY31 [36], OsWRKY22 [37], OsWRKY30 [38], OsWRKY28 [39], OsWRKY76 [40] and OsWRKY62 [41], have been implicated in immune responses against fungal and bacterial pathogens. Alternatively, some of the WRKY proteins have also been shown to play important roles in regulating abiotic stress tolerance (for review see [42]), such as Arabidopsis WRKY6 and WRKY75 in low phosphorus stress [43,44], WRKY25 and WRKY39 in heat stress [45,46], WRKY63 (ABO3) and WRKY57 in drought stress [47,48], WRKY34 in cold stress [49]), WRKY18, WRKY40, WRKY70 and WRKY54 in osmotic stress [50,51], WRKY30 in oxidative stress [52] and WRKY46 in aluminum toxicity [53], and rice OsWRKY30 in drought stress [54].…”
Section: Introductionmentioning
confidence: 99%
“…That increased resistance in both cases was also associated with activated expression of both salicylic acid (SA) and JA-related defense genes. Abbruscato et al (2012) found over-expression of OsWRKY22 lead to enhanced disease resistance to M. oryzae. Singh et al (2013) identified an elevated expression of native rice gene Osmyb4 (also coding for TFs) in disease resistant cultivars indicating its possible role in disease resistant regulating mechanism.…”
Section: Mirabilis Jalapamentioning
confidence: 97%